Winning big but feeling no better? The effect of lottery prizes on physical and mental health - Bénédicte Apouey; Andrew E. Clark (Institute for the Study of Labor (IZA), 2010)
We use British panel data to determine the exogenous impact of income on a number of individual health outcomes: general health status, mental health, physical health problems, and health behaviors (drinking and smoking). Lottery winnings allow us to make causal statements regarding the effect of income on health, as the amount won by winners is largely exogenous. Positive income shocks have no significant effect on general health, but a large positive effect on mental health. This result seems paradoxical on two levels. First, there is a well-known status gradient in health in cross-section data, and, second, general health should partly reflect mental health, so that we may expect both variables to move in the same direction. We propose a solution to the first apparent paradox by underlining the endogeneity of income. For the second, we show that lottery winnings are also associated with more smoking and social drinking. General health will reflect both mental health and the effect of these behaviors, and so may not improve following a positive income shock. This paper thus presents the first microeconomic analogue of previous work which has highlighted the negative health consequences of good macroeconomic conditions.
Keywords: D1; I1; I3; 330; Income; self-assessed health; mental health; smoking; drinking; Einkommen; Gesundheit; Psychische Störung; Glücksspiel; Gewinn; Großbritannien